Exploring the Influence of Social Environment on Mental Health, Behavioral Patterns, Leadership Development, and Interpersonal Relationships Among Youth in a Digitalized Society. - Галушка, Зоя Іванівна; Карп, Олександр Дмитрович; Тимчак, Віра Степанівна (International Journal of Organizational Leadership, 2025)
The study is devoted to the analysis of the influence of the social environment on the mental state, behavior, development of leadership qualities and formation of interpersonal interactions of the individual in the context of modern socio-cultural transformations. The key role of social support as a stress buffer and a factor of psycho- emotional stability, which directly affects cognitive and affective reactions, self-esteem and the ability to social adaptation, is established. The relationship between the perception of support, stress level and overall personality functioning in the youth environment, which is most vulnerable to the negative impact of social isolation, digital fragmentation and reduced intensity of interpersonal connections, is considered. The research methodology was based on a combination of quantitative and qualitative approaches: content analysis, statistical interpretation of standard coefficients, use of the multiple growth formula, and secondary analysis of empirical data. Five main domains ofinfluence of the social environment were identified: mental state, behavioral regulation,leadership potential, interpersonal interaction, and adaptability, which were the context of psychological mechanisms – emotional stability, self-control, self-esteem, and the level of social involvement. The results indicate a deep psychosocial destabilization among young people, which is manifested in a decrease in cognitive functions, emotional instability and difficulties in building socially effective behavioral models. The practical significance of the work is to formulate recommendations for optimizing the social environment as a factor of mental health. The expediency of strengthening family support, creating structures of compensatory social interaction and adapting psychoprophylactic strategies to the needs of young people is substantiated. Further research should focus on the study of neuropsychological mechanisms that influence the social context of mental functions and the development of structural interventions aimed at strengthening social capital and resilience in the face of chronic stress.
Keywords: Social security, Sustainable development, Social protection, Gender equality, Human and social capital